Exploring the Critical Barriers to the Implementation of Renewable Technologies in Existing University Buildings - Joaquín Fuentes-del-Burgo (MDPI AG, 2021)
For more than a decade, the European Union has been implementing an ambitious energy policy focused on reducing CO2 emissions, increasing the use of renewable energy and improving energy efficiency. This paper investigates the factors that hinder the application of renewable energy technologies (RETs) in existing university buildings in Spain and Portugal. Following a qualitative methodology, 33 technicians working in the infrastructure management offices of 24 universities have been interviewed. The factors identified have been classified into economic-financial, administrative and legislative barriers, architectural, urban planning, technological, networking, social acceptance, institutional and others. It is concluded that there have not been sufficient economic incentives to carry out RETs projects in this type of building. Conditioning factors can act individually or jointly, generating a greater effect. Most participants consider that there are no social acceptance barriers. Knowledge of these determinants can facilitate actions that help implement this technology on university campuses in both countries.